Characterization of hole taper in laser drilling of silicon nitride ceramic under water. Issue 11 (1st August 2018) - Chen, Qiang; Wang, Hong-Jian; Lin, Dong-Tao; Zuo, Fei; Zhao, Zhuang-Xin; Lin, Hua-Tay
Abstract: Nanosecond pulsed laser drilling of silicon nitride ceramic was conducted in air and under water to study the effects of laser scanning speed and processing environment on the hole taper. Results showed that drilling under water has a more profound impact to the hole taper than in air. The shape of cross-section was significantly different between two processing environments. In order to describe the curve shape under water, a novel characterization method was thus proposed to calculate taper angle as a function of the depth of holes. The taper angles decreased with increasing depth of holes at the fixed scanning speed and the similar tendency was also observed with decreasing scanning speed at the same depth of holes. The differences of element composition and surface roughness between air and under water were investigated. The present results suggested the better processing surface quality could be obtained by laser drilling under water.